2020
DOI: 10.1038/s41598-020-66534-4
|View full text |Cite
|
Sign up to set email alerts
|

An accurate and efficient method for occlusal tooth wear assessment using 3D digital dental models

Abstract: Tooth or material wear in a dentition is a common finding that requires timely diagnosis for management and prevention of further loss or associated esthetic or functional impairment. Various qualitative and quantitative methods have been suggested to measure tooth or material wear, but they present with limitations, such as imprecision, subjectivity, or high complexity. Here we developed and assessed an efficient 3D superimposition method to accurately measure occlusal tooth wear on 3D digital dental models. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
94
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 31 publications
(105 citation statements)
references
References 26 publications
9
94
1
1
Order By: Relevance
“…In line with previous research ndings testing the application of surface-based superimposition techniques in neighboring areas 10,36 , the present study concluded that the selection of the reference area considerably affects the outcomes. We showed that even small differences in the superimposition reference areas may have considerable effects.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In line with previous research ndings testing the application of surface-based superimposition techniques in neighboring areas 10,36 , the present study concluded that the selection of the reference area considerably affects the outcomes. We showed that even small differences in the superimposition reference areas may have considerable effects.…”
Section: Discussionsupporting
confidence: 89%
“…It should be noted that reproducibility in this study involved superimposition reference area selection, measurement area selection, and segmentation error. According to previous studies, without the last three sources of error, the reproducibility of the surface superimposition methods would have been perfect 3,10,18,[24][25][26]36 . When 3D photos are used instead of CBCT derived facial surface models, there is no segmentation error, though this is of limited extent 18 .…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Three dimensional surface imaging techniques have greatly expanded the possibilities for accurate, easily acquired, and risk free 3D facial imaging. The superimposition of serial 3D images consists a valuable tool for the evaluation of individual facial changes over time 4 , 5 , 9 , 38 . Among others, this facilitates treatment decision-making and prediction of outcomes for ongoing or future interventions.…”
Section: Discussionmentioning
confidence: 99%
“…The study tests the use of an intraoral scanner, which is a relatively new, but very powerful tool, added to the contemporary armamentarium of dental practitioners. Intraoral scans offer great possibilities for very accurate tooth wear assessment using 3D superimposition techniques [ 47 ].…”
Section: Discussionmentioning
confidence: 99%